Analysis of Crude Oil Production Using Gas Lift - genuinely, Ebigenibo; Kosisochukwu, Nwudoh Chisom (European Journal of Applied Sciences, 2022)
Gas lift is used to increase production by reduction in the density of the oil column in the tubing, reduction of the flowing bottom-hole pressure which is affected by the hydrostatic pressure of the fluid column and by providing external energy to the oil. In this study an oil field in the Niger Delta was used as case study; it has a production life span of over ten years with characteristics such as high gas-oil ratio (GOR) and high reservoir pressure which makes gas lift suitable for optimizing the wells. The aim of this study is to select the gas lift method suitable for optimum production in the wells using the production modelling softwares PROSPER, and GAP. Simulation studies were conducted using data from two wells in the oil field. The performance of continuous and intermittent gas lifted performance on two wells were compared. The results indicated that continuous gas lift system will be suitable for a well that has high flow rate and high GOR. Also, intermittent gas lift system will be suitable for a well that has lower reservoir pressure and low productivity. Sensitivity analysis of water cuts, gas injection rates and well head pressures were carried out to investigate how the wells will respond to changing operating conditions such as increasing water cut, increasing gas injection rates and increasing well head pressures in the future.